Perancangan Kebijakan Persediaan e-Commerce dengan Pertimbangan Permintaan Probabilistik dan Performance Score - Pujarani, Amanda Sekar; Pambudi, Hardian Kokoh; Setyawan, Erlangga Bayu (IAI Nasional Laa Roiba Bogor, 2024)
Julis, a local company focused on the production and sale of perfumes through e-commerce platforms, is one of the SMEs facing such challenges. Julis has encountered difficulties in managing its product inventory, leading to high inventory costs and low customer order fulfillment rates (fill rate). These issues risk hindering the company's growth and diminishing consumer trust. This research aims to design optimal inventory policies for Julis by considering probabilistic demand and the company's performance score. This performance score is a measure of performance that integrates two key criteria: profit, calculated based on total inventory costs, and fill rate. With the right inventory policies, Julis is expected to improve inventory efficiency, reduce costs—particularly ensuring inventory costs meet the target of less than 40% of the company's total revenue or income—and achieve a minimum fill rate target of 95%, which is considered crucial for maintaining customer satisfaction and supporting business growth.The approach used in this research is an inventory optimization model that combines probabilistic methods in determining Order Quantity (Q) and Reorder Point (ROP). This design aims to address demand uncertainty, which often poses a major challenge in inventory management within the e-commerce sector. Additionally, this research introduces the integration of inventory classification based on performance score, enabling the company to prioritize certain products based on relevant performance criteria. As a result, each product category can be managed more efficiently and strategically according to business priorities. The results of this research indicate that the implementation of the designed inventory policies can significantly improve Julis' performance score. Specifically, in terms of cost efficiency, these policies can reduce inventory costs and increasing the fill rate, which directly positively impacts the company's profitability. Furthermore, the integration of inventory classification based on performance score has also proven effective in helping Julis identify the most critical products to prioritize in its inventory management.